Feminismo e cidadania comunicativa: processos comunicacionais de coletivos feministas de Porto Alegre e Salvador - Guia, Bruna Lapa da (Universidade do Vale do Rio dos Sinos, 2021)
The thesis seeks to understand the communicational processes, uses and appropriations of digital territories by feminist collectives Odara – Black Woman Institute, Plural Female Collective and Olga Benário Women's Movement, From the cities of Porto Alegre and Salvador, from the perspective of building communicative citizenship linked to feminist struggle. The research adopts transmethodology as an epistemic perspective, which allowed the development of methodological, theoretical and empirical dimensions in articulation and mutual confluence and enabled interdisciplinary dialogue in the formation of theoretical arguments, from the areas of communication, sociology, philosophy and gender studies. Guided by this epistemological perspective, the thesis was built from research on research, context research, methodological research, exploratory research and empirical research movements. These articulated movements tensioned and shaped the production of theoretical problematizations about the potentials and risks of communication in digital spaces, multidimensional social networks, feminist movements, gender relations and communicative citizenship. In the exploratory phase, a mapping of feminist movements in Porto Alegre and Salvador was carried out, observation of the digital occupations of feminist movements in the two cities, observation and participation in collective actions and interviews with six communicating subjects, representatives of six feminist movements. These movements proved to be fundamental in the tensioning of theoretical arguments and in outlining the methodological movements of the systematic phase, which took place in a peculiar context of a global pandemic. This context caused decentralizations and social destabilization that permeated the methodological construction of the research and the observation of data obtained in the systematic phase. At this stage, from the perspectives of ethnography on the internet, observation of the uses and occupations of feminist movements in digital environments and semi-structured interviews with four research collaborators, representatives of the observed movements, were carried out, all mediated by digital platforms. The set of research processes pointed out that the observed movements have multimodal and multidimensional communicational practices that integrate and are crossed by digital and face-to-face environments. Communication is a constant, active and sometimes structural dimension of political actions and practices in the fight against sexism and the precariousness of women and for better lives. It was observed that these movements build actions of generosity and care for the subjects, paying attention to communication as a right in the formation of communicating subjects. Thus, it was perceived that the movements have the ability to build social technologies to care for the voice of the subjects, with the voice being used here as the ability to form their own free and liberating expression from hegemonic social oppression. In digital environments, these dimensions are translated into the uses and appropriations of platforms as territories suitable for sharing information regarding the demands and objectives of the struggle and actions of the movements; territories of disputed narratives and production of imaginaries resistant to the controlling images present in society; and spaces for social, cultural, political and epistemic empowerment. In summary, the data show that the observed feminist movements, when constructing social care technologies, based on gender as a structural element, produce sensitive communication centered on dialogue, and on the recognition of the subjects' autonomy and critical sense. Communicative citizenship is materialized in the understanding of the right to conditions for the development of on’sonw voice as a communicative right.
Keywords: Movimentos feministas; Cidadania comunicativa; Processos comunicacionais; Transmetodologia; Gênero; Feminist movements; Communicative citizenship; Communication processes; Transmethodology; Gender; ACCNPQ::Ciências Sociais Aplicadas::Comunicação